"Just do what you can […] make it work!" Exploring the impact of rapid population growth on police organizations in western North Dakota. Issue 4 (16th November 2015) - Dahle, Thorvald O.; Archbold, Carol A.
Abstract : Purpose: – The purpose of this paper is to examine how rapid population growth resulting from the oil boom affects police organizations in western North Dakota. Design/methodology/approach: – Using face-to-face interviews with 101 police personnel working in eight law enforcement agencies, this study explores how rapid population growth affects police organizations (in general), police resources, and the work environment of police organizations located in four counties in western North Dakota. Resource dependency theory and contingency theory provide a theoretical framework for understanding how changes in the communities (external environment) have led to changes within police organizations in this region. Findings: – Rapid population growth resulting from the oil boom in western North Dakota has required police agencies to make changes in the way that they are structured and function. In addition, the rapid increase in population has also strained police organizations' resources. Research limitations/implications: – The findings from this study may only be applicable to police organizations in western North Dakota. Interviews are based on police officers' perceptions. Practical implications: – Findings from this study suggest that police organizations in western North Dakota are currently experiencing a bad "fit" with their external environment. In order to get back to a good "fit" additional resources are needed from the state government. Social implications: – The number of calls for police service have increased dramatically since the oil boom began in 2008 in the Bakken region of western North Dakota. The addition of police officers and needed resources has not kept pace with the rapid population growth. The quality of police service to the public will decline if additional resources are not made available to police organizations. Originality/value: – This paper features the first and only study of the impact of rapid population growth on police organizations in western North Dakota. This study is both timely and important as the population growth in western North Dakota is predicted to continue for several decades into the future.